Accident Prone Area Database Analysis in Yogyakarta City - Hardimansyah, Rizki; Putro, Hanendyo; Rokhim, Abdul; Rahmita, Destria (RSF Conference Series: Engineering and Technology, 2022)
The need for transportation in Indonesia is increasing day by day. This is due to the high population growth, the rapid number of motorized vehicle ownership, as well as the construction of new settlements, which resulted in the need for transportation facilities always increasing. Transportation problems occur as traffic density increases, one of which is traffic accidents. As a first step in reducing the number of accidents, it is necessary to identify accident-prone areas. It is needed to compile a GIS-based traffic accident database that is informative. In this research, two methods of analysis are generally carried out, including analysis of traffic accident-prone areas and analysis in compiling a database based on geographic information systems. In this study, results were obtained regarding the characteristics of traffic accidents in the city of Yogyakarta which included the number of victims of traffic accidents during the period 2016 – 2020, as many as 3,530 people, with the type of vehicle involved in the most accidents being motorcycles, namely 3,671 vehicles. The type of front-rear collision is the most common type of accident and the age most often involved in accidents is in the age range of 20-29 years. Then based on the results of the analysis using three methods of determining DRK, including the equivalent accident number (EAN) method, the frequency method, and the z-score method, obtained five roads that are categorized as accident-prone areas, namely Jenderal Sudirman, Brigjend Katamso, HOS Cokroaminoto, Kusumanegara, and Magelang.